Wala Si Santanas Sa Ilalim Ng Lupa - Soco, Denmark B. (Likhaan: The Journal of Contemporary Philippine Literature; Vol 18 No 1 (2024): LIKHAAN 18 The Journal of Contemporary Philippine Literature, 2024)
During the Spanish colonization, Christianity spread throughout the Philippines, affecting the culture and faith of every Filipino. The church played a vital role in society, symbolizing salvation through the gospel. Moreover, the church served as a facade for oppressors, who feigned moral virtue and good intentions. In mining communities like Mt. Diwalwal, the church is among the most significant social structures. It offers hope to miners, who seek guidance, safety, and abundance from the Almighty. Edgardo M. Reyes in his novel Diwalwal: Bundok ng Ginto describes Diwalwal as a very different place. Here, the oppressed use the church to feed their egos and maximize their power. According to belief, Satan resides beneath the land. In mining community, the tunnel is the gateway to where the gold can be found. A symbolic representation of Satan’s dark domain, where miners extract gold. This personal essay aims to help people understand that Satan does not dwell beneath the land.